Fluorination of CF3CH2Cl over Cr-Mg fluoride catalyst: The effect of temperature on the catalyst deactivation - Lee, H; Jeong, HD; Chung, YS; Lee, HG; Chung, MJ; Kim, S; Kim, HS (ACADEMIC PRESS INC JNL-COMP SUBSCRIPTIONS, 1997)
The heterogeneous fluorination catalysts (Cr(OH)(x)F3-x) which have recently been employed for the synthesis of CF3CH2F (HFC-134a), were characterized by X-ray diffraction, infrared spectroscopy, and photoelectron spectroscopy. The IR study of these catalyst samples indicated that the amount of hydroxyl group in chromium phases decreases as the deactivation process proceeds. Pyridine adsorption experiments showed that these catalyst samples possess both Lewis and Bronsted acid sites and the strengths of Lewis acid sites diminish as the catalyst activity decreases. Elemental analyses and XPS revealed that the catalyst sample prepared at a higher reaction temperature contained larger amount of cokes that are believed to be the major cause of catalyst deactivation. The XPS analysis indicates that the carbon cokes appear to be carbidic carbons which are produced by the successive decomposition of reactants. In situ IR experiments were performed with CF3CH2Cl and CF2=CHCl to elucidate the pathway to coke formation. The activity quenching was observed for the alkali metal-doped catalyst, which supports the important role of Lewis acidity in the catalysis. (C) 1997 Academic Press.
Keywords: MAGNESIUM FLUORIDE; CHROMIUM-OXIDE; SURFACES; ESCA; CHEMISTRY; ALUMINUM; DECOMPOSITION; SPECTROSCOPY; DISMUTATION; IRON